Language Laboratory Use and the Development of a Self-Instructional Training Tape Program in Counsellor Education - Hum, Andrew; Calder, Peter; Zingle, Harvey W. (Canadian Journal of Counselling and Psychotherapy, 2012)
The primary purpose of this study was to determine the effectiveness of the use of the language laboratory to teach counselling skills. A 52-minute self-instructional training tape program was developed in which a basic element of empathy, reflection of feeling, was modelled. This self-instructional training tape program containing both video and audio components was developed utilizing Bandura's modeling concepts and the principles of simulation, role-practice, and playback. One hundred and four senior education students were randomly assigned to one of five groups. These groups were: (1) Language Labora- tory Audio Group, (2) Language Laboratory Video and Audio Group, (3) Audiotape Recorder Group, (4) Lecture-Discussion Group, and (5) No-Treatment Control Group. The results showed firstly that the language laboratory is neither inferior or superior to other instructional media and secondly that the self-instructional tape program is an effective procedure for teaching counselling skills.